Correction: Myeloproliferative leukemia protein activation directly induces fibrocyte differentiation to cause myelofibrosis. Issue 12 (December 2018) - Maekawa, T.; Osawa, Y.; Izumi, T.; Nagao, S.; Takano, K.; Okada, Y.; Tachi, N.; Teramoto, M.; Kawamura, T.; Horiuchi, T.; Saga, R.; Kato, S.; et al.
Owing to the insufficient specificity of the anti-myeloproliferative leukemia protein (MPL) antibody in the original version of this Article, Figure 6 and parts of Figures 2a, 4e, and 5a do not represent the correct information. The corrected version of Figure 6 is in this correction and those of Figures 2a, 4e, and 5a are shown in the supplemental information.